Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531712
|View full text |Cite
|
Sign up to set email alerts
|

Designing for the deluge

Abstract: Social media are a potentially valuable source of situational awareness information during crisis events. Consistently, "digital volunteers" and others are coming together to filter and process this data into usable resources, often coordinating their work within distributed online groups. However, current tools and practices are frequently unable to keep up with the speed and volume of incoming data during large events. Through contextual interviews with emergency response professionals and digital volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…For instance, although citizen-reported data on Twitter is a potential data source for emergency responders [62], the data are so abundant that they require intense information processing operations such as filtering and extracting [34]. Emergency response professionals and digital volunteers have to collaboratively filter and process social media data into usable resources during crisis events [12], which can be time and resource intensive.…”
Section: Icts and Crisis Responsementioning
confidence: 99%
“…For instance, although citizen-reported data on Twitter is a potential data source for emergency responders [62], the data are so abundant that they require intense information processing operations such as filtering and extracting [34]. Emergency response professionals and digital volunteers have to collaboratively filter and process social media data into usable resources during crisis events [12], which can be time and resource intensive.…”
Section: Icts and Crisis Responsementioning
confidence: 99%
“…The Australian Bureau of Statistics suggested this may be due to the rise of informal volunteering aided by digital solutions (Australian Bureau of Statistics, 2017). Online digital platforms have transformed volunteerism (Liu, Harrison, Lai, Chikoto, & Jones-Lungo, 2016) in a range of contexts, such as natural disaster and crisis management (Cobb et al, 2014), collaborative online content creation on platforms such as Wikipedia (Kuznetsov, 2006), and hotlines which are considered 'emotional band aids' for individuals in distress (Gilat & Latzer, 2016). Organisations such as United Nations Volunteers have online platforms to help people volunteer their desired skills for various charitable projects all around the world (www.…”
Section: Digital Volunteerismmentioning
confidence: 99%
“…Earlier studies related to this field assessed existing platforms and tools and thereby developed alternative ones. Some of these studies developed platforms that can support the activities of volunteers in tracking, organising, visualising and reporting actionable information (Cobb et al, 2014;Gupta et al, 2014). Reuter et al (2015) work examined the use of existing social media tools, platforms and approaches among volunteer communities to understand the challenges associated with their use in crisis management.…”
Section: Appropriation Of Collaborative Technologiesmentioning
confidence: 99%
“…For example, during the 2007 Southern California wildfires a study revealed how users that were geographically dispersed leveraged ICT to build community resources and find community-specific information (Shklovski, Palen and Sutton, 2008). As for studies that examine the appropriation of tools by the established groups, their focus tended to revolve around highlighting the type of tools without emphasizing on how their use enabled or constrained disaster response (Starbird and Palen, 2013;Cobb et al, 2014).…”
Section: Appropriation Of Collaborative Technologiesmentioning
confidence: 99%